2016
DOI: 10.1177/1468794115579474
|View full text |Cite
|
Sign up to set email alerts
|

Hiring the experts: best practices for community-engaged research

Abstract: Community-engaged approaches to research and practice continue to show success in addressing health equity and making long-term change for partnership relationships and structures of power. The usefulness of these approaches is either diminished or bolstered by community trust, which can be challenging for partnerships to achieve. In this research note we present an example process for recruiting, interviewing, and hiring community researchers as a starting place for capacity building and for laying the founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 18 publications
1
41
0
Order By: Relevance
“…In general terms, co-production can help challenge power asymmetries whilst adding depth and breadth to academics’ and community members’ understandings of their cultures [ 31 ]. Hardy et al [ 31 ] have shown how co-production approaches can minimize health inequalities when they are implemented from the outset, invest in participants (training and support), and select participants through experience and potential (not only via qualifications).…”
Section: Co-produced Research With User/community Groups: What Is mentioning
confidence: 99%
See 1 more Smart Citation
“…In general terms, co-production can help challenge power asymmetries whilst adding depth and breadth to academics’ and community members’ understandings of their cultures [ 31 ]. Hardy et al [ 31 ] have shown how co-production approaches can minimize health inequalities when they are implemented from the outset, invest in participants (training and support), and select participants through experience and potential (not only via qualifications).…”
Section: Co-produced Research With User/community Groups: What Is mentioning
confidence: 99%
“…In general terms, co-production can help challenge power asymmetries whilst adding depth and breadth to academics’ and community members’ understandings of their cultures [ 31 ]. Hardy et al [ 31 ] have shown how co-production approaches can minimize health inequalities when they are implemented from the outset, invest in participants (training and support), and select participants through experience and potential (not only via qualifications). Equally, in his participatory action research with older gay men in Hong Kong, Kong [ 21 ] has demonstrated how the emergence of a collaborative approach during the research process can transform the researched to researcher in the shift “from hierarchy to collaborative partnership” (p. 9).…”
Section: Co-produced Research With User/community Groups: What Is mentioning
confidence: 99%
“…Participatory study (9)(10) with a qualitative approach developed in the group dynamic of Creative and Sensitive Method (CSM), a type of inquiry based on art (11) . In participatory studies, knowledge is produced in the collective space, experiences are shared, and participants work actively from the perspective of their social reality.…”
Section: Study Typementioning
confidence: 99%
“…The map provides a starting point for discussion and data analysis. Hardy et al (2014) explained the benefits of this mapping toolkit as a time effective way to gather a variety of data from a group of participants. This resource allows for the “elicitation of unanticipated data” (p. 6) and enables researchers to connect with participants who may otherwise be unlikely to share their thoughts.…”
Section: Cultural Safety Uptakementioning
confidence: 99%